2017
DOI: 10.1080/02786826.2017.1321102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of size and shape on filtration of TiO2 nanoparticles

Abstract: Titanium dioxide (TiO 2 ) is one of the most widely used nanoscale materials to date and could result in human exposures. The main objective of this study was to perform detailed characterization of TiO 2 agglomerate particles and how these properties influence particle penetration in a screen filter. Transmission electron microscope (TEM) photos showed compact agglomerates of nanoscale primary particles. The projected area diameter was close to the mobility diameter, where the length was about 25% larger than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The first parameter to be studied was the size of the airborne nanoparticles. Numerous studies, conducted with screen and nonwoven filters, report an increase in penetration as the electrical mobility diameter is increased, with a Most Penetrating Particle Size (MPPS) greater than 300 nm [25], [26]. In the present work, minimum penetration was reached at 24% for nSiO2-30 nm and 26% for nSiO2-300 nm (Figure 4).…”
Section: Effect Of Sizesupporting
confidence: 53%
See 1 more Smart Citation
“…The first parameter to be studied was the size of the airborne nanoparticles. Numerous studies, conducted with screen and nonwoven filters, report an increase in penetration as the electrical mobility diameter is increased, with a Most Penetrating Particle Size (MPPS) greater than 300 nm [25], [26]. In the present work, minimum penetration was reached at 24% for nSiO2-30 nm and 26% for nSiO2-300 nm (Figure 4).…”
Section: Effect Of Sizesupporting
confidence: 53%
“…He concluded that the filtration efficiency is higher for agglomerates than for spheres. On the other hand, Chang and Zhou (2017) evaluated and modeled the effect of size and shape of 25 nm-TiO2 nanoparticles on the filtration through a screen filter (solidity 0.345 and face velocities at 2.92 and 5.85 cm/s) [26]. Their conclusion confirmed Kim's work.…”
Section: Introductionmentioning
confidence: 63%
“…The total interactive energy likely has a stronger inuence than the particle size on the stability of NPs in aquatic environments. 48 The variations indicate that aggregation and agglomeration are constant processes during the settling period, and even though the size of the particles may change, the average size distribution remains between 100 nm and 300 nm ( Fig. 4).…”
Section: Particle Size Distribution Over Timementioning
confidence: 95%
“…The grain size of the synthesized TiO 2 nanostructure was calculated using the intercept technique [8].…”
Section: Theoretical Considerationmentioning
confidence: 99%